Bahasa Inggris - Santoso, Heni Rachmawati; Novayani, Wenda; Lestari, Indah; Putri, Afifah (Jurnal Komputer Terapan, 2024)
The Community Health Center Queue Management System is an Android and website-based online queuing system. The purpose of this research is to help Puskesmas Umban Sari who faces difficulty in managing patient queues. The main process handled by the system is registration and data recapitulation. The system has two queuing features that can be activated or not as needed, namely the priority queue and linear queue. The development method in this research is done by using the Rational Unified Process (RUP). The tests carried out are black box testing, usability testing, and performance testing. Based on the outcomes obtained from black box testing, it can be determined that the system is functioning very well. The Usability testing with a total of 50 respondents shows a score of 84%, which means that this system is quite satisfactory and useful for users. Whereas in performance testing, the Load Testing and Stress Testing processes were obtained by 67%, which means that the performance of this system is quite good when given heavy pressure and many users access simultaneously. The system successfully reduced waiting times and improved service efficiency.